THE NEWLY DEVELOPMENT IN LARGER VESSEL’S SIZE CREATING IMPACTS TOWARDS GLOBAL ENVIRONMENT - R.T Wing Shin; M.H. Abdul Rahman (Marine Frontier, 2021)
The shipping industry is one of the most important and most frequently used means of transportation in the world of export and import trade involving the shipping of goods between countries as the shipping industry holds 90 percent of the world's consumers. Demand for the use of shipping industry services is increasing every day as many advantage factors are offered such as the cost of shipping goods which is much cheaper than air transport and offering shipment with a larger capacity of goods such as bulk cargo which creates competition between shipping industry owners. Meanwhile, containerships currently face various challenges due to Covid-19 pandemic such as excess container delay, low shipping rates, increasing fuel costs, and eco-efficient policies to restrict virus spread where a good business strategy is needed to ensure logistics movement keep running. The ship size is getting bigger and new generation of container ship are made in order to fully optimize the operation and bring more profit to the company. They can support capacity in excess of Twenty-foot equivalent unit (TEU) per single load for instance is OOCL Hong Kong which is the latest upgraded container ship where it can carry up to 21,413 TEU full capacity. For sure the increase in the size of ships used in the international shipping industry will provide more endurance, save operating costs and lead to a greater economic result when interacting with a world of trade where economies of scale are achieved especially during this lockdown period. However, for some reason the bigger the ship size, the more problems it caused towards environmental pollution. Larger vessels will increase competition in the shipping industry as this means less consumption rate of the ship, but this is the trend in the industry, and soon larger vessels built and into service. There is something to consider in advance. The goals of this paper are to identify impacts created by Mega ships that are widely used nowadays in shipping industry towards environments health, its consequences in future and finding solutions to overcome it. Obviously once ships size grown bigger it will bring more pollution towards environment and that is the solid reason of why this paper need to be done. This paper will solely be focused on secondary data which is relying on journals, articles and internet references. Data collected will be summarized in order to give clear understanding to the reader regarding the impact of ship size towards environment. The finding of this study is expected to be a good reference for all researcher and logistic industry players.